Mapping cellular processes that determine delivery of plasmid DNA to the nucleus: application in Chinese hamster ovary and human embryonic kidney cells to enhance protein production - Budge, James D. (Frontiers in Bioengineering and Biotechnology, 2025)
Delivery of DNA into nucleated eukaryotic cells is known as transfection and has been essential in establishing technologies such as recombinant protein production and gene therapy. Considerable research efforts have led to development of a variety of transfection methods for a multitude of applications and cell types. Many methods are efficient in delivering DNA across the plasma membrane but few focus on subsequent delivery into the nucleus, a necessary step in expression of a recombinant transgene, and the cellular processes governing nuclear import of DNA during transfection have proved elusive. Herein, live confocal microscopy was used to track plasmid DNA during transfection of Chinese hamster ovary (CHO) and human embryonic kidney (HEK) cells to map key cellular processes central to nuclear import of DNA showing that there is a strong relationship between events of cell division, promotion of DNA dispersal from endosomes and subsequent nuclear import leading to gene expression. Furthermore, cationic lipid-mediated transfection is more dependent on events of the cell cycle than electroporation to deliver DNA into the nucleus. These findings have informed the design of a method where both CHO and HEK cells are synchronised at G2 phase of the cell cycle followed by timely release enabling cell cycle progression to maximise the frequency of division events immediately after transfection. This led to a 1.2–1.5 fold increase in transfection efficiency for polyethylenimine (PEI) mediated and electroporation transfection respectively. This process enhanced production yields of a monoclonal antibody 4.5 fold in HEK and 18 fold in CHO cells in the first 24 h post transfection. Overall, this study elucidated key cellular processes fundamental to transfection of CHO and HEK cells providing knowledge which can be applied to DNA delivery technologies in a plethora of fields.